Meshing Principle of Offset Asymmetric Face Gear and Precise Design of Complex Conjugate Tooth Surface - Shuai Mo; Wenjie Tang; Shengping Zhu; Zongxiang Yue; Hanjun Gao (Jixie chuandong)
According to the theory of gear space meshing， the space coordinate system of gear meshing is established， the mathematical models of asymmetric involute cylindrical gear and offset face gear are derived， and the meshing equation of asymmetric offset face gear is established. Taking the meshing equation as constraint condition， the numerical calculation program for solving the tooth surface point cloud coordinates of offset face gear pair is compiled， and the tooth surface point cloud coordinates of offset face gear pair are solved. The complex surface model of offset face gear is obtained by fitting the point cloud. The problems that the inner diameter of asymmetric offset face gear is not undercut and the outer diameter is constant are studied， and the limiting condition of tooth width is determined. The basic design parameters of offset face gear pair are determined， the discrete coordinate points of tooth surface are solved and imported into 3D software. The accurate geometric models of offset face gear and asymmetric involute gear are established. The research result has guiding significance for the design and manufacture of special asymmetric offset face gear transmission system.